Variação espaço-temporal da fertilidade do solo e decomposição da matéria orgânica numa floresta ripária na guarnição da aeronáutica de Pirassununga (SP) - Fernandes, Pedro Henrique de Godoy (2020)
The Atlantic Rainforest is a heterogeneous phytogeographic domain, considered one of the 36 hotspots for global conservation, however only 26% of its original forest cover remains. The Seasonal Semideciduous Forest (SSF) is a phytophysiognomy of the Atlantic Rainforest that presents two well-marked climatic periods, composed of a period of intense rain in the summer and a period of low precipitation and mild temperatures. The plant communities in these environments are partially constituted by semideciduous species, which lose their leaves in the dry season. In this phytophysiognomy, the nutrient cycling is closely linked to the deposition of litter, since it is a key element in maintaining fertility in an ecosystem after decomposition. When next to watercourses it is called Riparian Forest, extending between the limit of watercourses to the edge of higher lands. Proximity to water resources plays an important role in water quality and mitigation of anthropic actions that could damage the ecosystem. Nevertheless, it has been considered as one of the most degraded in the world. In these regions, the hydric regime constantly influences the processes involved in the soil fertility. In view of this, the present study consists of two chapters, in which in the first, we simultaneously evaluate the spatial variation between chemical attributes of the soil in an area of a continuous Riparian Forest to a SSF, and the temporal variation between the end of the dry season and the end of the rainy season in soil chemical attributes. In the second chapter, we evaluated the variation in clay content and soil moisture in the same area as in Chapter 1, and simultaneously the effect of nutrient availability in the soil and the structure of the forest on the rate of decomposition and the stabilization factor, using the method of Tea Bag Index. To collect soil samples, measure vegetation structure and perform the Tea Bag Index protocol, five plots of 10 x 10 m to 5 m from the Mogi-Guaçu River (R) were demarcated, and five plots 25 m distant from the watercourse (I). The analysis showed that the most distant areas from the watercourse (I) were more fertile, due to the higher clay content. At the end of the wet season, soil fertility is greater when compared to the end of the dry season, suggesting that litterfall contributes strongly to maintaining fertility. The decomposition rate did not differ between regions, but it tended to be higher in the dike (R) region, probably due to the higher microbial activity. The stabilization factor was higher in the inner forest (I), suggesting that areas with a more homogeneous canopy, higher humidity and a greater amount of exchangeable cations, mainly base saturation, promote greater carbon fixation in the soil, when compared with areas more stratified and with more sandy soils. Therefore, the conservation of forest areas is extremely important in mitigating one of the most serious current problems in society, climate change.